Phytohustil® and root extract of Althaea officinalis L. exert anti-inflammatory and anti-oxidative properties and improve the migratory capacity of endothelial cells in vitro - Bonaterra, Gabriel A.; Schmitt, Johanna; Schneider, Kim; Schwarzbach, Hans; Aziz-Kalbhenn, Heba; Kelber, Olaf; Müller, Jürgen; Kinscherf, Ralf (Frontiers in Pharmacology, 2022)
Introduction: Althaea officinalis L.'s root extract (REA) has been used as a medicinal plant since ancient times to treat a cough. Applying REA leads to a protective film that induces a faster regeneration of the lesioned laryngopharyngeal mucosa caused by dry coughs. The buccopharyngeal mucosa is a highly vascularized tissue. In this regard, anti-inflammatory/-oxidant phytochemicals that improve the repair of the lesion site, e.g., neovascularization in the wound, are critical for promoting healing. For this reason, it is essential to investigate the effects of Phytohustil® and REA on different cellular components of the mucosa under conditions similar to those found in the injured mucosa. Thus, this in vitro study investigated the anti-inflammatory/oxidative and pro-migratory properties of Phytohustil® cough syrup on vascular endothelial cells. Methods: Human umbilical vein endothelial cells (HUVEC) were pretreated (24h) with Phytohustil®, its excipients, or REA, followed by incubation with hydrogen peroxide (H2O2;1h; pro-oxidative) or with lipopolysaccharides (LPS; 3h; pro-inflammatory). Viability and cytotoxicity were measured by PrestoBlue® assay. Intracellular reactive oxygen species (ROS) were quantified with 20-70-dichlorofluorescein diacetate (DCFDA). The release of interleukin 6 (IL6) was determined by enzyme-linked immunosorbent assay (ELISA). The migratory capacity of HUVEC was measured using a scratch assay. Results: Our results show that Phytohustil®, its excipients and REA were not cytotoxic. Pretreatment of HUVEC (24h) with Phytohustil® or REA inhibited the LPS-activated IL6 release. Phytohustil® or REA inhibited the H2O2-induced cytotoxicity and intracellular ROS production. Phytohustil® and REA significantly stimulated the wound closure compared to control. Conclusions: Our data show that Phytohustil® and REA have anti-inflammatory/-oxidant properties and improve the migratory capacity of vascular endothelial cells. These properties may contribute to the healing characteristics of Phytohustil® and support the benefit of Phytohustil® in patient's treatment of irritated oral mucosa.